Effects of implementing exercise programs on patients diagnosed with gonarthrosis prior to total knee arthroplasty - a systematic review - Ferreira, Silvana Fonseca (2021)
Osteoarthritis is the most common condition that affects the knee joint, and i tis considered a leading cause of disability. When conservative treatment fails, surgery may be recommended. Exercise programs are na importante tool in the management of knee osteoarthritis (OA) and in total knee arthroplasty (TKA) rehabilitation and, when implemented in a preoperative contexto, are thought to optimize postoperative outcomes. To determinate the effects of implementing exercise programs on patients diagnosed with gonarthrosis prior to TKA on pain, function and/ or quality of life (QoL). A literature search of Randomized Controlled Trials (RCTs), published from 2015 until 2020, was conducted across four databases. Eligibility criteria were applied. Individual studies were evaluated using PEDro and OCEBM scales. Risk of bias assessment was also performed. Eight studies were included. RCTs compared control groups with preoperative exercise (n=5), combined preoperative exercise and education (n=2) and preoperative exercise in hospital versus at home (n=1). The studies collected data regarding self-reported outcomes and performance-based outcomes. A conclusive answer could not be given although it was seen a not significant general favor of this interention as a safe and cost-effective option.